Towards an Island-based Narrative of the Western Mediterranean Borderscape – Continental Islands as Condensers and Laboratories - Isabella Traeger (European Journal of Creative Practices in Cities and Landscapes, 2024)
This article proposes to contribute towards this aims by analysing through a borderscaping approach the remote micro-islands and enclaves which constitute the EUro-mediterranean Southern border, namely Ceuta, Melilla, the Canary Islands, Gibraltar and the Pelagie islands. The article examines these territories as precursors and testing grounds in the implementation of ‘Fortress EUrope’; before focusing on their historical role as core of highly-integrated cross-border regions. It concludes on the potential of these territories as testing grounds of novel trans-Mediterranean narratives and political practices.